2016
DOI: 10.1161/jaha.115.003188
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 for Prediction of Heart Failure and Cardiovascular Death in an Elderly, Community‐Dwelling Population

Abstract: BackgroundSoluble ST2 (sST2), a marker of myocyte stretch and fibrosis, has prognostic value in many cardiovascular diseases. We hypothesized that sST2 levels are associated with incident heart failure (HF), including subtypes of preserved (HFpEF) and reduced (HFrEF) ejection fraction, and cardiovascular death.Methods and ResultsBaseline serum sST2 was measured in 3915 older, community‐dwelling subjects from the Cardiovascular Health Study without prevalent HF. sST2 levels were associated with older age, male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 54 publications
4
56
0
2
Order By: Relevance
“…This was true for both patients with dyspnea as well as those with acute heart failure[36]. In a recent study, Parikh et al[37] studied population of community-dwelling older individuals enrolled in the Cardiovascular Health Study. They found that soluble ST2 levels were significantly associated with incident heart failure, cardiovascular death and that greater ST2 level was continuously associated with increasing hazard for cardiovascular death[37].…”
Section: St2mentioning
confidence: 99%
See 2 more Smart Citations
“…This was true for both patients with dyspnea as well as those with acute heart failure[36]. In a recent study, Parikh et al[37] studied population of community-dwelling older individuals enrolled in the Cardiovascular Health Study. They found that soluble ST2 levels were significantly associated with incident heart failure, cardiovascular death and that greater ST2 level was continuously associated with increasing hazard for cardiovascular death[37].…”
Section: St2mentioning
confidence: 99%
“…In a recent study, Parikh et al[37] studied population of community-dwelling older individuals enrolled in the Cardiovascular Health Study. They found that soluble ST2 levels were significantly associated with incident heart failure, cardiovascular death and that greater ST2 level was continuously associated with increasing hazard for cardiovascular death[37]. Various studies have documented the incremental value of addition of ST2 to pre-existing predictive models of heart failure[37,38].…”
Section: St2mentioning
confidence: 99%
See 1 more Smart Citation
“…sST2 level was found to be a useful biomarker of non‐response to GVHD therapy and improved risk stratification according to clinical grade . Meanwhile, baseline serum sST2 had good predictive value for heart failure and myocardial infarction of all subtypes and cardiovascular death in a large community‐dwelling population. These findings support our finding that elevated baseline sST2 level is associated with poor prognosis in ESRD patients who experience PDF.…”
Section: Discussionmentioning
confidence: 97%
“…Much work has also been conducted to establish associations between ST2 levels and clinical outcomes before and after cardiovascular procedures in specific populations 47, 48, 49, 50. The individual and combined predictive power of these 3 biomarkers, in addition to boost in predictive ability they have provided to existing preoperative models of mortality and risk in many cardiovascular conditions and procedures, merited their congruent consideration in a multi‐marker model aimed at preoperatively predicting in‐hospital mortality in patients after CABG 51, 52, 53…”
Section: Discussionmentioning
confidence: 99%